Fine‐root decomposition characteristics of four typical shrubs in sandy areas of an arid and semiarid alpine region in western China - He, Ling‐Xianzi (Ecol Evol, 2019)
BACKGROUND AND AIMS: Research into the variability of fine‐root decomposition and nutrient cycling processes in arid and semiarid ecosystems is highly significant not only for investigations of regional and global carbon and nitrogen cycling but also for offering a theoretical basis for vegetation restoration and reconstruction. In particular, information is limited on fine‐root decomposition processes and nutrient releasing characteristics in the high‐altitude Qinghai Gonghe basin, which has different tree species and variable fine‐root diameters. MATERIALS AND METHODS: Four types of Salicaceae and Caragana shrubs were selected at the Qinghai Gonghe desert ecosystem research station. The litterbag method was adopted to measure decomposition rates of fine‐roots with three diameter classes (1–2 mm, 0.5–1 mm, and 0–0.5 mm). Chemical analysis was performed to determine nutrient (C, N, P, and K) concentrations of fine‐root, and nutrient release rates were compared among fine‐roots with different diameters during different decomposition periods. The differences in mass residual ratio and nutrient release rate among different diameter classes were studied with one‐way ANOVA. RESULTS: Fine‐root decomposition rates were in the order Caragana intermedia > Caragana korshinskii > Salix psammophila > Salix cheilophila. Fine‐root decomposition showed a trend of “fast‐slow‐fast” variation, and decomposition rate increased as the diameter of fine‐roots increased, irrespective of tree species. During the decomposition process, the nutrients C, N, and P of fine‐root were in a release state for the four shrubs with different fine‐root diameters, and the corresponding release rates of Caragana shrubs were higher than those of Salicaceae shrubs. Release rates of nutrients C and N accelerated as fine‐root diameter increased, whereas release rates of nutrients P and K had no observed relation with fine‐root diameter. Fine‐root decomposition ratio was significantly correlated with initial values of N, P, C/N, C/P, and N/P of fine‐root. Fine‐root mass loss ratio was significantly correlated with initial concentration of soil nutrient K, and the correlation was positive for fine‐roots with diameters of 0–0.5 mm and 0.5–1 mm; however, no other significant correlation was observed between fine‐root mass loss ratio and initial soil environmental factors within this study. CONCLUSIONS: Our study showed that tree species and fine‐root diameter strongly affected decomposition rates, whereas diameter class exerted little effect on nutrient release rates.